Effect of spray-drying and extrusion on physicochemical characteristics of sweet potato starch - dos Santos, Thaís Paes Rodrigues [UNESP] (2019)
This study aimed to understand the physicochemical characteristics of sweet potato starch following spray-drying and extrusion processes for desirable applications. Spray-dried starch showed formation of agglomerates and decreased in average granular size from 16.5 μm of the native starch granules to 14.1 μm. Spray-drying reduced the percentage crystallinity from 25.3 to 22.6% and showed a slight decrease in the molecular weight of amylopectin from 3.1 to 2.6 × 108 g mol−1. In addition, changes in the pasting and gelatinization properties, higher final viscosity (454.4 RVU), and less enthalpy change (8.73 J g−1) were reported after spray-drying. Thus, spray-drying resulted in partially gelatinized starch, which can be selected for making more viscous products. Extruded sweet potato starch displayed an amorphous structure, showed total loss of crystallinity, and significant reduction in molecular weight of amylopectin to 0.41 × 108 g mol−1, reflecting complete gelatinization of starch granules during extrusion. Extruded starch showed significant changes in pasting properties, including a display cold viscosity (9.4 RVU). Therefore, extruded starch was suitable for products that require quick solubility and a low final viscosity. Thus, the spray-drying and extrusion processes produce sweet potato starches with particular characteristics that can be used for different and potential applications in industries.